Analysis of the Influence of Work Flexibility, Financial Compensation, and Employee Empowerment on Employee Job Satisfaction at PT Propan Raya ICC Palembang - Wulandari, Rika; Lazuarni, Shafiera; Kurniawan, Mohammad (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the influence of work flexibility, financial compensation, and employee empowerment on job satisfaction at PT Propan Raya ICC Palembang. The background of this research is based on the phenomenon occurring within the company, where employees are beginning to demand more than just competitive salaries they also seek flexible working arrangements, fair compensation, and opportunities to be empowered in their roles. Based on interviews with several employees, it was found that rigid working systems, perceived unfair compensation, and limited autonomy negatively impact job satisfaction. This research adopts a quantitative approach using a survey method, with questionnaires distributed to 85 respondents, representing the total population used as the study sample. The results of multiple linear regression analysis show that both partially and simultaneously, the three independent variables work flexibility, financial compensation, and employee empowerment have a positive and significant effect on job satisfaction. These findings support Maslow's hierarchy of needs theory, which states that job satisfaction is achieved when employees’ needs from basic to self-actualization are fulfilled. This research is expected to serve as a reference for PT Propan Raya ICC Palembang in formulating more adaptive, fair, and empowering work policies to enhance employee satisfaction and loyalty. Keywords: Work Flexibility, Financial Compensation, Employee Empowerment, Job Satisfaction.